Desarrollo de la creatividad - Mírez Tarrillo de Delgado, Perpetua del Socorro (2023)
The objective of the study is to analyze the state of the art in the development of creativity in five-year-old preschoolers. For this, a qualitative investigation was applied, with a hermeneutic and documentary method. Seventeen scientific articles related to the theme developed in the Scopus, Scielo, Dialnet, Redalyc, Latindex and Google Scholar databases were selected and analyzed. It is concluded that it is possible to develop the creativity of five-year-old children by promoting challenging activities of interest to the student, one of them being brain gymnastics.